Development of a Size Targeted Formulation to Treat Pulmonary Arterial Hypertension - Swainson, Sadie M E (2020)
The aim of this thesis is to develop a novel formulation for the treatment of Pulmonary Arterial Hypertension (PAH). PAH is a rare but serious disease which is invariably fatal without treatment. Vascular remodelling and an increase in vascular resistance lead to increased pulmonary arterial pressure and right ventricular overload, which ultimately result in right-sided heart failure and death. While treatments are available for PAH, they suffer from a lack of proven effect on mortality, serious administration problems and systemic side effects which can have a significant effect on patients’ quality of life.